Hubungan Motivasi dan Kebiasaan Belajar terhadap Hasil Belajar Siswa Sekolah Dasar Negeri Kelas V pada Pelajaran Matematika di Kecamatan Sagulung - Fatimah, Siti; Prabawanto, Sufyani; Adji, Sandra Sukmaning (STKIP PGRI Bandar Lampung, 2022)
State Primary School students in Sagulung district became the location of this research with the theme the relationship of motivation and learning habits toward to student achievement of fifth grade state primary school students. By involving teachers and students in Sagulung District as the population as well as the research sample. The method used is descriptive quantitative by looking at the description of the test results using statistical data to obtain the research results. The data collection techniques used observations, and questionnaires in which all the answers were analized. The research instrument was calibrated by using the validity and reliability coefficients. Validity was tested by using product moment correlation, while the research data were analyzed by using correlation techniques with multiple linear regression equations and path analysis. The results of research show that the testing done between motivation and Students' learning habits togetherly were indicated by the value of FCount is 39,252, while the value of Ftable = 3,097 because the Fcount > Ftable, it can be concluded that this study has a significant effect. While the value of the contribution of this research was 68.9% where the student achievement variable was explained by motivation and learning habits, while the remaining 31.1% was explained by other variables which is not examined in this research.